Evaluación de la viabilidad del uso de la tiourea utilizando SO2 y agentes oxidantes, para disminuir el consumo de tiourea y aumentar el porcentaje de recuperación de oro 2013 - Narváez Holguín, Ernesto (2013)
The present research studies the extraction of gold by acid leaching method with constant stirring from a gold ore from the district Pataz (Act 2.5 Oz Au / TM ) evaluating two variables: The influence of the addition of SO2 and the concentrations of two oxidizers , Ferric Sulfate ( as oxidizing agent ) and cupric sulfate pentahydrate ( as oxidizing catalyst ) thiourea consumption and percentage of gold extraction . The particle size of the ore was 70 % - 200 m and the tests were performed in the mineral processing laboratory of the Academic Department of Metallurgical Engineering. In the experimental part 27 tests were performed according to the two-factor design , and performing analysis of variance must be more significant variable in the extraction of gold for this research is the concentration of ferric sulfate and cupric sulfate pentahydrate , plus the best gold extraction results were obtained under the following conditions : Concentration of thiourea [ Your ] = 2g/l and concentration of ferric sulfate [Fe2(SO4)3] = 4g / l. Attainment of a gold extraction of up to 92 % of Au . And the lower consumption of thiourea was obtained when the concentration of thiourea [ Your ] = 2g/l and concentration of cupric sulfate pentahydrate [ CuSO4-.5H2O ] = 4g / l. Turning to a minimum consumption of 2.632g / l. Demonstrating that this method of acid leaching with constant stirring in the presence of ferric sulfate and cupric sulfate is feasible to process gold ores since most gold mining , the lower consumption of thiourea at a short reaction rate is obtained